Isolation and Screening of Streptomyces spp from Soil Samples of Ekiti State University Nigeria for Antibacterial Activity - Omidoyin, Kehinde Caleb; Femi-Ola, Titilayo Olufunke (International Journal of Research Innovation and Entrepreneurship, 2020)
Actinomycetes are a versatile group of procaryotes that exist in all habitats and are widely distributed in all types of the ecosystem including the soil, water, and sediments obtained from deep sea. This group of gram-positive bacteria, especially the Streptomyces is widely known to produce a variety of secondary metabolites, including antibiotics and other therapeutically useful bioactive molecules. Therefore, the isolation and identification of new strains is crucial for the production of desirable antibiotics. The aim of this study was therefore to isolate and identify novel strains of Streptomyces exhibiting a high antibacterial activity. To achieve this objective, 60 actinomycetes colonies were isolated in pure cultures from different soil samples within Ekiti State University, Nigeria, and 12 isolates which showed a high antibacterial activity against test organisms were selected. The selected actinomycetes isolates were characterized for morphological and biochemical identifications. Analysis of morphological and biochemical characteristics indicated that all the 12 selected isolates exhibiting antibacterial properties belonged to the genus Streptomyces. Five (41.7%) of the Streptomyces isolates produced diffusible pigments of different colors. Moreover, screening of the isolates with regard to their antimicrobial activity against test bacteria indicated that all the Streptomyces isolates exhibited antimicrobial activity against at least two of the test organisms while eight isolates (66.7%) were found to have moderate to high antimicrobial activity. Two (16.7%) of the Streptomyces isolates were active against all the test organisms while the highest antibacterial activity based on zone of inhibition was observed in Klebsiella spp. with an inhibition zone of 18mm. Since 20% of the actinomycetes isolates in this study showed inhibitory effects against indicator bacteria, it was suggestive that soil of Ekiti State University, Nigeria could be used as an interesting source to be explored for novel Streptomyces strains with high potency of antimicrobial production.